An Assessment Strategy Using Visual Basic Application in PowerPoint: A Free Interactive Quiz Application for ICT Class - Ahillon Jr, Ricardo Cruz; Aquino, Paulo Martin M. (Universitas Pendidikan Indonesia (UPI), 2023)
Assessment of learning is one vital phase in the teaching-learning process inside the classroom. Assessment has been improving since there are various ways how to conduct the assessment. Here the purpose of this study was to demonstrate an assessment strategy using a visual basic application in PowerPoint. It can be classified as a free interactive quiz application for the ICT class. The findings revealed that the assessment tool was a valid and acceptable evaluation tool since it is evaluated as very much acceptable by the teachers. The assessment strategy using Visual Basic Application was a valid and acceptable evaluation tool by the teachers in terms of instruction, discussions, pictures used, and activities. The study recommends that learners be exposed to assessment strategies using the Visual Basic Application for a fast, convenient consolidation of their scores and evidence of true assessment.